The Role of Indigenous in Maintaining Traditional Ritual and Transfer Knowledge to Next Generation - Nurhayati, Titi; Wahyudin, Uyu; Saripah, Iip; Pramudia, Joni Rahmat (GoAcademica Research & Publishing, 2025)
The role of women is very important in instilling the noble values of motherhood culture and noble values that must be preserved even though the times have changed where there are modernization challenges. Responding to globalization while maintaining the noble values of culture requires efforts to cultivate and form characters that are able to adapt to changes while maintaining local wisdom, because education is actually a civilizational process that cannot be separated from the role of women to realize it. This research aims to find out the role of indigenous women in maintaining traditional rituals and providing knowledge to the next generation in Kesepuhan Sinar Resmi. This field research uses survey or observation methods in the field, interviews with Ambu (traditional leaders) and Abah (traditional leaders), and Focus Group Discussion (FGD) with 12 traditional leaders and elders to obtain data as a primary source. The research approach used is a sociological, historical, and normative approach. The participation of women can be seen in the daily life of the indigenous people of Kasepuhan Sinar Resmi in maintaining and implementing the noble cultural values of their community